A REGRESSION TREE FOR IDENTIFYING RISK FACTORS FOR FEAR OF FALLING: THE INTERNATIONAL MOBILITY IN AGING STUDY (IMIAS). (16th November 2018) - Curcio, C; Wu, Y; Vafaei, A; Fernandez de Souza, J; Guerra, R; Guralnik, J; Gomez, F
Abstract: Background: We determine the best combination of factors for predicting the risk of developing Fear of Falling (FOF) in community-dwelling older people via Classification Regression Tree (CaRT) analysis. Methods: Participants of International Mobility in Aging Study (IMIAS). Community-dwelling older adults living in Canada: Kingston (Ontario), Saint-Hyacinthe (Quebec); Albania (Tirana); and Latin America: Natal (Brazil), Manizales (Colombia). In 2014, 1, 725 participants (aged 65- 74) were assessed. With a retention rate of 81%, in 2016, 1, 409 individuals were reassessed. These risk factors for FOF were entered into the CaRT: age, sex, education, self-rated health, comorbidity, body mass index, medication, visual impairment, frailty, cognitive deficit, depression, fall history, and Short Physical Performance Battery (SPPB) total scores, walking aid use, and mobility disability measured by the Nagi questionnaire. Results: The classification tree included 12 end-groups representing differential risks of FOF with a minimum of two and a maximum of five predictors. The first split in the tree involved impaired physical function (SPPB scores). Respondents with less than 8 in SPPB score and mobility disability had 82% risk of developing FOF at the end of 2 years follow-up. In respondents with no impaired physical functioning, the risk of developing FOF varied between 4% and 39.8%. Predictors in this branch of the tree were 'low level of education', 'poor self-rated health' and 'living with non-spouse persons'. Conclusion: This classification tree included different groups based on specific combinations of a maximum of five easily measurable predictors with emphasis on impaired physical functioning risk factors for developing FOF.